Artemisia Species with High Biological Values as a Potential Source of Medicinal and Cosmetic Raw Materials - Halina Ekiert; Marta Klimek-Szczykutowicz; Agnieszka Rzepiela; Paweł Klin; Agnieszka Szopa (Molecules, 2022)
Artemisia species play a vital role in traditional and contemporary medicine. Among them, Artemisia abrotanum, Artemisia absinthium, Artemisia annua, Artemisia dracunculus, and Artemisia vulgaris are the most popular. The chemical composition and bioactivity of these species have been extensively studied. Studies on these species have confirmed their traditional applications and documented new pharmacological directions and their valuable and potential applications in cosmetology. Artemisia ssp. primarily contain sesquiterpenoid lactones, coumarins, flavonoids, and phenolic acids. Essential oils obtained from these species are of great biological importance. Extracts from Artemisia ssp. have been scientifically proven to exhibit, among others, hepatoprotective, neuroprotective, antidepressant, cytotoxic, and digestion-stimulating activities. In addition, their application in cosmetic products is currently the subject of several studies. Essential oils or extracts from different parts of Artemisia ssp. have been characterized by antibacterial, antifungal, and antioxidant activities. Products with Artemisia extracts, essential oils, or individual compounds can be used on skin, hair, and nails. Artemisia products are also used as ingredients in skincare cosmetics, such as creams, shampoos, essences, serums, masks, lotions, and tonics. This review focuses especially on elucidating the importance of the most popular/important species of the Artemisia genus in the cosmetic industry.